Liberté de presse écrite au Maroc : L’évolution au regard de l’évaluation - Mohamed Naimi (L’Année du Maghreb)
This article aims to examine the press freedom situation in Morocco and his evolution since 2011 with regard to evaluation on national and international levels. While the international NGO specialized in that domain, in particular Freedom House (FH) and Reporters without Borders (RWB), was overwhelming Morocco, the Moroccan official authorities held rather an apologist speech and displayed by reflex the image of a free press. For approaching the real press freedom situation in Morocco, it seems interesting to grasp the differences of goals and methods of these evaluations, before confronting them with practices and feeling of the people principally concerned: the Moroccan journalists. In order to evaluate evolution of that freedom, it is up to examine alternately, in light of journalists survey, both systems of evaluation, the one established by the international organizations and the other one provided by Moroccan official authorities.